Apresiasi Ahmad Musțāfa Al-Marāġī Dalam Menafsirkan Q.S Al-Fātihah - Sohibi Harahap, Ali Musolli; Syafruddin, Syafruddin; Harahap, Amiruddin Tayib (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Appreciation arises from the attitude of a commentator in evaluating an event/object of stud. It also appears as a way to get the deepest meaning in a work. Namely by studying and understanding in depth. Meanwhile, interpreting activities are also included in the appreciation section, because in interpreting you have to carry out an in-depth study first. This study aims to find out how a commentator, Ahmad Musțafa Al-Marāġī, appreciates letters in the Qur’an. This discussion focuses on Q.S Al-Fātihah in the book Tafsīr Al-Marāġī. Because, Ahmad Musțafa Al-Marāġī, in interpreting Q.S Al-Fātihah, first gives appreciation before studying the verses in more depth. Therefore, the author discusses this study with the title